1996
DOI: 10.1096/fasebj.10.8.8666166
|View full text |Cite
|
Sign up to set email alerts
|

Neuroprotection by melatonin from kainate‐induced excitotoxicity in rats

Abstract: In this study, we injected 10 mg/kg kainate i.p. into rats. This resulted in a brain injury, which we quantified in the hippocampus, the amygdala, and the pyriform cortex. Neuronal damage was preceded by a set of typical behavioral signs and by biochemical changes (noradrenaline decrease and 5-hydroxyindoleacetic acid increase) in the affected brain areas. Melatonin (2.5 mg/kg) was injected i.p. four times: 20 min before kainate, immediately after, and 1 and 2 h after the kainate. The cumulative dose of 10 mg/… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
96
1
1

Year Published

1997
1997
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 154 publications
(103 citation statements)
references
References 3 publications
5
96
1
1
Order By: Relevance
“…A relationship between melatonin, corticotrophic and opioid peptides and brain benzodiazepine receptors has been also reported (14,15). Recent studies have shown the ability of melatonin to counteract both kainate-and N-methyl-D-aspartate (NMDA)-induced excitotoxicity (16)(17)(18). Inhibition of the NMDA receptor activity by melatonin depends, at least partially, on its effect to reduce nitric oxide synthase activity, thus decreasing the amount of nitric oxide produced by the NMDA activation (19).…”
Section: Introductionmentioning
confidence: 96%
“…A relationship between melatonin, corticotrophic and opioid peptides and brain benzodiazepine receptors has been also reported (14,15). Recent studies have shown the ability of melatonin to counteract both kainate-and N-methyl-D-aspartate (NMDA)-induced excitotoxicity (16)(17)(18). Inhibition of the NMDA receptor activity by melatonin depends, at least partially, on its effect to reduce nitric oxide synthase activity, thus decreasing the amount of nitric oxide produced by the NMDA activation (19).…”
Section: Introductionmentioning
confidence: 96%
“…Administration of glutamate receptor agonists is a commonly used method to investigate activity-dependent events in the CNS, such as neural apoptosis, synaptic plasticity, and neurogenesis in the hippocampus [14][15][16]. For example, administration of KA induces neuronal apoptosis in pyramidal neurons in the CA1-3 region [14].…”
Section: Discussionmentioning
confidence: 99%
“…For example, administration of KA induces neuronal apoptosis in pyramidal neurons in the CA1-3 region [14]. KA administration is also known to cause mossy fiber sprouting and up-regulation of KA receptor density that consequently leads to the modification of glutaminergic synaptic transmission in the hippocampus [16].…”
Section: Discussionmentioning
confidence: 99%
“…Some of the most toxic agents which have been utilized and shown to be counteracted by melatonin include the excitatory neurotransmitter analogue kainic acid (71)(72)(73), H202 (74,75), potassium cyanide (76), lipopolysaccharide (60,77,78), hydrophobic bile acids (79), carbon tetrachloride (61), and the carcinogen safrole (63,64). Also, the damage caused by a physical agent, i.e., ionizing radiation (65,80), and a highly destructive experimental procedure known to generate free radicals, i.e., induced ischemia followed by reperfusion (81)(82)(83), has been shown to be reduced by concurrent melatonin administration.…”
Section: Melatonin As An Antioxidantmentioning
confidence: 99%